A novel super-cooled humidification?dehumidification system driven by thermal vapour compression unit for seawater desalination. (10th September 2008) - Saadawy, Mahmoud; Karameldin, Aly; Negeed, El-Sayed
The current study presents the concept of a novel seawater desalination system that is configured by a humidification?dehumidification unit based on the vapour-compression process (HDDTVC). The coupled refrigeration unit employs the thermal compression of vapour by a jet-ejector. The new technical idea of proposed desalination system depends mainly upon the creation of a super-cooled temperature under the ambient condition (near 0°C) for the dehumidification process, instead of using the heat sink in the cooling process. Subsequently, the significant development in the unit performance is achieved by increasing its availability owing to the condensation and collection of the dew from the atmospheric vapour as an additional source of water production, in addition to the product from the main source of seawater. A computer program based on a simulation mathematical model is constructed and a comprehensive analysis is discussed for the new system. The alternate novel process is characterised with the ability to recuperate the retrogressive water production in traditional process, where the productivity of freshwater may increase up to eight times compared with the conventional humidification?dehumidification process applied for the countries with hot and tropical climatological conditions. The amount of extracted and retrieved water from dew in most humid regions can reach around 51% and 37% of the new unit production. In this investigation, enhancement of the unit performance is the main objective. The influence of changing the characteristics of the jet-ejector (the cornerstone of the thermal refrigeration vapour-compression unit) on the system performance is discussed and analysed so as to clarify the controlling parameters. Also, the applicability of different working fluids is tested for the vapour compression process. Based on the current work, the new HDDTVC is suggested as a promising unit of medium-scale commercial production to provide arid and isolated communities with their requirements for potable water.